(untitled) (Ustozlar uchun, 2026)
The development of economic thinking and awareness enables the ability to think in terms of modern economic science, which plays a crucial role in the development of entrepreneurship. One of the key roles of youth in the economy is the development of human capital. By acquiring education, professional skills, and practical experience, young people become qualified specialists capable of working effectively in various sectors of the economy. The quality of human capital directly impacts labor productivity, innovation, and the pace of economic development. Young people are quicker to embrace modern technologies, actively implement digital solutions, and participate in the creation of new products and services. Many successful startups and innovative projects are created by young entrepreneurs who offer innovative approaches to solving economic and social problems.